Psychological effects of implantable cardioverter defibrillator shocks. A review of study methods - Manzoni, Gian Mauro; Castelnuovo, Gianluca; Compare, Angelo; Pagnini, Francesco; Essebag, Vidal; Proietti, Riccardo (Frontiers in Psychology, 2015)
Background: The implantable cardioverter defibrillator (ICD) saves lives but clinical experience suggests that it may have detrimental effects on mental health. The ICD shock has been largely blamed as the main offender but empirical evidence is not consistent, perhaps because of methodological differences across studies. Objective: To appraise methodologies of studies that assessed the psychological effects of ICD shock and explore associations between methods and results. Data Sources: A comprehensive search of English articles that were published between 1980 and 30 June 2013 was applied to the following electronic databases: PubMed, EMBASE, NHS HTA database, PsycINFO, Sciencedirect and CINAHL. Review Methods: Only studies testing the effects of ICD shock on psychological and quality of life outcomes were included. Data were extracted according to a PICOS pre-defined sheet including methods and study quality indicators. Results: Fifty-four observational studies and six randomized controlled trials met the inclusion criteria. Multiple differences in methods that were used to test the psychological effects of ICD shock were found across them. No significant association with results was observed. Conclusions: Methodological heterogeneity of study methods is too wide and limits any quantitative attempt to account for the mixed findings. Well-built and standardized research is urgently needed.